The nexus of environmental, social, and governance practices with the financial performance of banks: A comparative analysis for the pre and COVID-19 periods - Muhammad Zahid; Syeda Um-Ul-Baneen Naqvi; Amin Jan; Haseeb Ur Rahman; Said Wali (Cogent Economics & Finance, 2023)
This study aims to examine the impact of ESG practices on the financial performance of the banking industry of Pakistan during the pre and COVID-19 periods. The data were collected from the annual reports of selected banks for the pre-COVID-19 period (2018) and the COVID-19 period (2020). Results of the t-test show that there is a significant difference in ESG disclosures between the pre and during-COVID-19 periods. The regression analysis shows that the formative ESG factor positively affected the financial performance of the banking industry during the pre-COVID-19 period. While the reflective factors (environmental and social) positively affected the financial performance of the banking industry in the pre-COVID-19 period. During the COVID-19 period, the formative factor of ESG was found to have a significant positive impact on the financial performance of the banking industry. Similarly, in this period, the reflective factors (social and governance) were also found to have a significant positive impact on the financial performance of the banking industry. Interestingly, environmental sustainability negatively impacted the financial performance during the COVID-19 period. It indicates that the banking industry ignored environmental sustainability practices during the COVID −19 period, negatively affecting their financial performance. It suggests that ignoring environmental sustainability practices will deteriorate financial performance following the COVID-19 period. These results have profound policy implications for practitioners and policymakers in the banking industry, which are discussed.
Keywords: 330; banking industry; COVID-19; disclosures; environmental; financial performance; governance; social